2020
DOI: 10.1007/jhep02(2020)195
|View full text |Cite
|
Sign up to set email alerts
|

Are “Superentropic” black holes superentropic?

Abstract: We study a critical limit in which asymptotically-AdS black holes develop maximal conical deficits and their horizons become non-compact. When applied to stationary rotating black holes this limit coincides with the "ultraspinning limit" and yields the Superentropic black holes whose entropy was derived recently and found to exceed the maximal possible bound imposed by the Reverse Isoperimetric Inequality [1,2]. To gain more insight into this peculiar result, we study this limit in the context of accelerated A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 99 publications
(197 reference statements)
1
18
0
Order By: Relevance
“…Recently, a new class of so-called ultra-spinning black holes [18][19][20][21] in which one of their rotation angular velocities is boosted to the speed of light, has received considerable interest and enthusiasm. This kind of black hole solutions which can exist in arbitrary dimension D ≥ 4 have a noncompact horizon topology but with a finite area, and are asymptotically (locally) AdS with horizons being topologically spheres with two punctures at the north and south poles.…”
Section: Jhep11(2021)031mentioning
confidence: 99%
“…Recently, a new class of so-called ultra-spinning black holes [18][19][20][21] in which one of their rotation angular velocities is boosted to the speed of light, has received considerable interest and enthusiasm. This kind of black hole solutions which can exist in arbitrary dimension D ≥ 4 have a noncompact horizon topology but with a finite area, and are asymptotically (locally) AdS with horizons being topologically spheres with two punctures at the north and south poles.…”
Section: Jhep11(2021)031mentioning
confidence: 99%
“…Up to date, a lot of new superentropic black hole solutions [27][28][29][30][31] from the known rotating AdS black holes have been obtained so far. Very recently, it has been found that the superentropic black hole can also be obtained by running a conical deficit from the usual rotating AdS black hole [32]. In addition, other aspects of the superentropic black holes, including thermodynamic properties [21,27,[29][30][31][33][34][35], horizon geometry [23,27,29], geodesic motion [24], Kerr/CFT correspondence [28][29][30], and so on, have been investigated consequently.…”
Section: Introductionmentioning
confidence: 99%
“…One is (2 + 1)-dimensional charged Banados-Teitelboim-Zanelli (BTZ) black hole which is the simplest [18][19][20][21][22]. Another important super-entropic black hole is a kind of ultraspinning black hole [23][24][25].…”
Section: Introductionmentioning
confidence: 99%